Frozen Section Library: Breast - Mohsin, Syed K.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
The Frozen Section Library series provides concise, user-friendly, site specific handbooks that are well illustrated and highlight the pitfalls, artifacts and differential diagnosis issues that arise in the hurried frozen section scenario. Frozen Section Library: Breast provides an easy reference and pocket book about the nuances of adequately handling breast specimens in a fashion that meets the increasingly complex environment of breast pathology. The pros and cons of frozen section versus use of touch imprint as well as related quality assurance requirements are addressed. Other less common uses of intraoperative evaluation, such as diagnosis and margin evaluation are described. The volume includes recommended guidelines for evaluation and documentation of specific gross pathologic features, in conjunction with radiological imaging. Techniques and protocols for such examinations are illustrated. The volume closes with an overview of the newly published guidelines for handling a variety of breast specimens, which are intended to be used for assessment of predictive factors. Syed K. Mohsin, M.D. is the Head of Breast Pathology and Medical Director, Immunohistochemistry, Riverside Methodist Hospital, Columbus, OH
Preface -- Sentinel Lymph Nodes -- Assessment of the Surgical Margins -- Diagnostic Evaluation of a Breast Mass -- Handling of Specimens with a Non-Palpable Lesion -- Core Needle Biopsies -- Regulatory Requirements for Breast Specimens -- Suggesting Reading.
Keywords: Medicine; Pathology; Medicine & Public Health; Pathology